Comparison of different ways of expressing creatine kinase concentration of soccer players during a competitive season - Daniel Barbosa Coelho; Christian Emmanuel Torres Cabido; Victor Augusto Lemos Ciminelli; Leonardo Gomes Martins Coelho; Lenice Kapes Becker; Emerson Cruz de Oliveira; Emerson Rodrigues Pereira; João Carlos Bouzas Marins; Emerson Silami Garcia
Abstract The aim of this study was to analyze the responses of creatine kinase [CK] expressed in different forms to the training load of professional soccer players during a competitive season. Twelve players (age, 24 ± 4 years) participated in the study. [CK] was analyzed before the pre-season (Pre), after the pre-season (Post), and in the competitive mesocycles (M1, M2, and M3). Results showed [CK] in the Pre, Post, M1, M2, and M3 phases in absolute values (181.3 ± 58.7, 416.4 ± 155.7, 526.4 ± 268.0, 403.8 ± 137.0, and 442.5 ± 212.3 U/L, respectively), relative values (16.3 ± 4.6, 39.5 ± 19.1, 47.8 ± 20.1, 37.5 ± 14.2, 40.1 ± 17.4 %CKmáx, respectively), and values relative to the variation delta (19.9 ± 3.6, 48.1 ± 26.5, 57.0 ± 23.2, 45.1 ± 17.7, and 48.3 ± 22.0 %ΔCKmáx, respectively). [CK] was lower only during the Pre phase compared to the other phases (p < 0.05). [CK] was expressed as %CKmáx or %ΔCKmáx may be more specific to monitor training. In addition, the individualization of this biomarker optimizes the athletes' performance as muscle injuries can be prevented.